The effects of cognitive behavioral therapy-based digital therapeutic intervention on patients with alcohol use disorder - Lim, Song-Hee; Shin, Jae-Kyoung; Ahn, Moo Eob; Lee, Chang-hyun; Lee, Sang-Kyu (Frontiers in Psychiatry, 2025)
IntroductionThis study investigated the effectiveness of a digital therapeutic intervention for individuals with alcohol use problems. Digital interventions are increasingly considered viable alternatives or complements to traditional face-to-face treatments, especially in improving accessibility and adherence.MethodsA total of 30 outpatients were recruited and randomly assigned to either a digital intervention group or a face-to-face cognitive behavioral therapy (CBT) control group. After excluding two dropouts, data from 28 participants were analyzed. The digital intervention group received a 12-week mobile application-based CBT program, which included 84 video-based CBT sessions. The control group received an 8-session standardized face-to-face CBT program over the same period. Both groups were also provided with a mobile application that included a diary feature for tracking alcohol consumption, cravings, and mood. Assessments were conducted at baseline, mid-treatment (week 4), and post-treatment (week 12) to evaluate risky drinking, craving, readiness for change, depression, anxiety, and alcohol-related symptoms.ResultsThe primary outcome, abstinence rate during weeks 9–12, was significantly higher in the digital intervention group (73.3%) compared to the control group (30.8%). Regarding secondary outcomes, the digital group showed significantly greater reductions in risky drinking, craving, and anxiety levels compared to the control group. However, no significant group differences were found for other outcome variables.DiscussionThese findings suggest that digital CBT-based interventions can be an effective alternative to face-to-face CBT for reducing alcohol use and related symptoms. The study highlights the potential of digital therapeutics in addiction treatment, while acknowledging limitations such as small sample size and short follow-up period. Future research should explore long-term effects and broader clinical applicability.Clinical trial registrationhttps://cris.nih.go.kr/cris/search/detailSearch.do?seq=29717&status=5&seq_group=29562&search_page=M, identifier KCT0010289.